Double coconut - A unique giant palm from Seychelles - Neema, M; Veluru, Aparna; Prakash, Krishna (Indian Horticulture, 2021)
The double coconut is a unique palm endemic to the Seychelles islands. These palm trees can live up to 1,000 years and bear the largest fruits and leaves in the entire plant kingdom. The plant is very slow growing as the palm seed takes 2 years to germinate and double coconut fruit is reported to take 6-7 years to develop. The palm possesses a unique water harvesting system as the large leaves catch water and channel it to their stalks, or petioles, which are scoopshaped like rain gutters and in this way, soil beneath the palm is kept moist while the distant soils are drier. Various fruit parts are used in traditional systems of medicine besides other use of palm-products. Traditionally, there was a practice of presentation of double coconut as a gift among the members of royal family as a symbol of prosperity. Until recently, the double coconut fruit-seeds were traded illegally due to high demand in the international market. Due to habitat loss and over-collection, the double coconut palm is considered endangered by IUCN Red List of Threatened Species. In India, the 125-year-old female double coconut tree, the lone specimen in India is dying and scientists are trying to save the palm as well as its maturing fruits.